Supporting Sleep - Nordin, M. author. aut Link
VI, 97 p.
Keywords: Social support and sleep are both health promoting factors and important in the prevention of illness and sick-leave. Promoting healthy work by providing good conditions for strong social relationships and by preventing bullying or harassment can improve sleep and consequently employee health, increasing work productivity and efficiency overall.